Study of Mean Platelet Volum When Exposed to Ultrasound Waves for Hypertension Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Platelets are one of the most important cells in human blood, and help control bleeding. Mean plateletvolume (MPV) play a vital role to indicate the activation of platelets. any significant changes of meanplatelet volume will effect on platelet activity. Vibration-stimulats changes in the platelets activity as a typeof stress upon MPV. This study aimed to investigate the impact of ultrasound waves on MPV of healthy andhypertension subjects in vitro model study. Venous blood samples obtained from healthy subjects (n=43 )and hypertensive patients (n=61 ) have been exposed to ultrasound waves for two periods (5-10) minutes.The MPV was measured using the Coulter electronic count (Complete blood Count). The results have beenshowen that ultrasound waves caused a significant changes MPV in healthy subjects and hypertensivepatients. The changes in the MPV are dependently related to the exposure time. In healthy subjects, the MPVshave been significantly increased by 12.6% for 10-min exposure while in hypertensive are significantlydecreased by 9.1% for 10-min. It concludes that ultrasound induced an increase of the MPV, and this effect istended to be less in patients with hypertension indicated that the responses of platelets are reduced in chronicdiseases. It is clearly indication that the cellular response of MPVs in hypertension patients were very weakmay because of hypertension. Whereas, MPVs response of healthy subject remained normal and effective.